Characterization of Exponential and Power Function Distributions Using sth Truncated Moments of Order Statistics - Afify, Ahmed; Ahmed, A. N.; Nofal, Z. M. (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
Characterization results have great importance in statistics and probability applications. New characterizations of Exponential and Power Function distributions are presented using the sth conditional expectation of order statistics in terms of their failure (hazard) rate. Our results generalize some of the known results of Ahsanullah (2009). A simulation study has been conducted to help an engineer or a practitioner to check whether the underlying distribution belongs to the hypothesized family.